# Precalculus with Trigonometry

posted by .

Prove or disprove the following Identities:

cos(-x) - sin(-x) = cos(x) + sin (x)

sin raised to the 4 (theta) - cos raised to the 4 (theta) = sin squared (theta) - cos squared (theta)

cos (x+(pi)/(6)) + sin (x - (pi)/(3)) = 0

cos(x+y)cos(x-y) = cos squared (x) - sin squared (y)

Sorry if you don't understand anything

• Precalculus with Trigonometry -

For the first problem:

cos(-x) - sin(-x) = cos(x) + sin(x)

A few identities for negatives:

cos(-x) = cos(x)
sin(-x) = -sin(x)

Therefore:

cos(x) - [-sin(x)] = cos(x) + sin(x)

==================================

cos(x+y)cos(x-y) = cos^2(x) - sin^2(y)

Some identities:
cos(x+y) = cos(x)cos(y) - sin(x)sin(y)
cos(x-y) = cos(x)cos(y) + sin(x)sin(y)

Multiplying using both identities:

[cos^2(x) cos^2(y)] - [sin^2(x) sin^2(y)]

Next, use the identity:
sin^2(x) + cos^2(x) = 1

[1-sin^2(x)][1-sin^2(y)] - [sin^2(x) sin^2(y)]

Multiply [1-sin^2(x)][1-sin^2(y)]:

1 - sin^2(y) - sin^2(x) + [sin^2(x) sin^2(y)] - [sin^2(x) sin^2(y)]

We are left with this:
1 - sin^2(y) - sin^2(x)

Which equals this:
cos^2(x) - sin^2(y)

===================

I'll stop there. I hope this helps.

## Similar Questions

2. ### Mathematics - Trigonometric Identities

Let y represent theta Prove: 1 + 1/tan^2y = 1/sin^2y My Answer: LS: = 1 + 1/tan^2y = (sin^2y + cos^2y) + 1 /(sin^2y/cos^2y) = (sin^2y + cos^2y) + 1 x (cos^2y/sin^2y) = (sin^2y + cos^2y) + (sin^2y + cos^2y) (cos^2y/sin^2y) = (sin^2y …
3. ### Calculus

I wanted to confirm that I solved these problems correctly (we had to convert the polar curves to Cartesian equations). 1.rcos(theta)=1 x=1 2.r=2*sin(theta)+2*cos(theta) r^2=2rsin(theta)+2rcos(theta) x^2+y^2=2y+2x (a little unsure …
4. ### trigonometry

can you correct the rest for me please? Express each as a function of theta: a. sin (270deg + theta)= cos theta b. cos (pi + theta)= -cos theta c. tan (810 + theta)= ?
5. ### trigonometry

can you correct the rest for me please? Express each as a function of theta: a. sin (270deg + theta)= cos theta b. cos (pi + theta)= -cos theta c. tan (810 + theta)= ?
6. ### Algebra II

Multiple Choice Which expression is NOT equivalent to 1?
7. ### Precalculus 2

Similiarly to a question I asked previously I took the same approach. the problem is: what value(s) of theta solve the following equation?
8. ### math(Trigonometry)

sin 2 theta + cos theta = 0 so, we use sin 2 theta = 2 sin theta cos theta right?
9. ### Trigonometry

Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …
10. ### Trigonometry

Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …

More Similar Questions